(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
This study investigates the role of reflective practices in enhancing student-centered language learning. Reflective practices, which involve learners in evaluating their learning processes, are increasingly recognized as tools to promote autonomy, critical thinking, and active engagement. This research draws on qualitative observations and learner feedback in English as a Foreign Language (EFL) contexts to examine how reflective techniques support personalized learning experiences and improve language acquisition outcomes. The results show that students who engaged in regular reflection were more motivated, took greater responsibility for their learning, and demonstrated measurable language progress.